Prevalence of depression and its associated factors among type 2 diabetes mellitus patients in a selected primary care clinic in Kuantan, Pahang - Md Aris, Mohd Aznan; Tin, Myo Han; J, Ahmad Hafizuddin; I, Mohd Shafeeq; MY, Mohd Khairulahnaf (2014)
Introduction : Depression is one of the most common mental health disorders in Malaysia. it occurs at any age and disease. it also has an increasing trend among patients with chronic illness including diabetes mellitus. the objectives of the study were to determines the prevalence of depression and its associated risk factors among patients with type 2 diabetes mellitus who attended a primary care clinic. methods : a cross-sectional study was carried out. the participants were selected through random sampling from a list of patient who attended the diabetics clinic in selected primary clinic care in kuantan, Pahang during the period from 1 July 2013 until 31 August 2013. the data were collected using a questionnaire comprising two parts. the first part consists of demographic and clinical characteristics of patients. the seconds part screened the presence of depression among the participants with diabetes mellitus by using the validated Depression and Anxiety Stress Scale 21 ( DASS21) Malay version. Results: A total of 103 participants were enrolled and the prevalence of depression in this was 12.6%. the study also revealed that depression is significant different with gender(21.2% vs. 3.9%) and history of recent significant life event ( 33.3% vs 9.1%) conclusion: the result indicate that female patients with type 2 diabetes mellitus or those with a history of recent significant life event have a higher risk of suffering from depression and need greater attention from primary care providers.